Between culture and culte, the Institut des Cultures d'Islam is 'here'. Issue 2 (January 2018) - Milne, Anna-Louise
Abstract : This article offers three intersecting perspectives on the creation and work of the Paris Institut des Cultures d'Islam (ICI): the discursive positioning and media reception of this unprecedented institution, the successive phases of its design and building, and its recent approach to arts programming. It identifies contradictory impulses operating in the ICI's symbolic valorization of the 'horizontal' relations of the city and its unswerving commitment to a categorical distinction between culture and culte . This double imperative has taken form, it suggests, in the foregrounding of the demonstrative claim 'here', which has served to exclude some of what was 'there' in the mix of the street, particularly street prayers, resulting in further marginalization of aspects of the Muslim religious practice in response to which it was created. Yet the ICI has also enabled new proximities between faith and secular arts programming. The article concludes on what this 'mixed' assessment of the first ten years of the ICI means for how we map the locations of 'culture' today.